Disabled person: construction of concept by this population - Pagliuca, Lorita Marlena Freitag; Oliveira, Paula Marciana Pinheiro de; Mariano, Monaliza Ribeiro; Silva, Jacqueline Mota da; Almeida, Paulo Cesar de; Oliveira, Giselly Oseni Barbosa (Rev Rene, 2015)
Objective: to build the concept of disabled person. Methods: study of analysis of concept using the phases field work and statistical analysis with 120 individuals divided into three groups of 40 people with hearing, visual and motor disability. Results: there was predomination of men (68%), 18-29 years old (55%), with superior education (35%) and married/common-law married (75%). The attribute accepted was person with limitation and still able to perform activity, with a difference between groups (p = 0.018); the keyword accepted was limitation (p = 0.001); the expression was disabled person, with intergroup difference (p = 0.013). Concept of choice by group was deaf (97.51%); blind (45%) and person with visual disability (45%) and; person with physical disability (27.5%). Conclusion: attributes, keywords used in the literature and public policy were not accepted. They prefer to be called deaf; blind or visually impaired; They reject people with motor disability and wheelchair user.